Congress in the Administrative State - Brian D. Feinstein (Washington University Law Review, 2018)
In an era of increased concern over presidential power, congressional oversight of the executive branch constitutes a substantial—but underappreciated—means of influencing agency decision-making. Scholars too often have overlooked it, and Congress is sub-optimally designed for its provision, but oversight has a significant impact on agency behavior. This Article provides a corrective. It presents the legal mechanisms that give oversight hearings their force and situates these hearings in their historical and legal context. In light of this framework and historical practice, the Article posits that ex post oversight hearings facilitate political control over the administrative state. Because oversight gets its bite from an implicit threat of legislative sanctions should an agency not change its behavior following hearings, however, committees’ decisions whether to pursue oversight hinge on the credibility of this threat. To test this theory, the Article introduces an original dataset of over 14,000 agency “infractions,” i.e., agency actions that are potential subjects of hearings. Analysis of these data reveals, first, that oversight is most likely to occur when the particular preference alignment of Congress, the relevant committee, and the agency make the threat of new legislation credible. A second empirical analysis finds that, when oversight hearings do occur, they can get results; infractions that are subject to hearings are 18.5% less likely to recur compared to otherwise similar infractions that are not subject to hearings. These findings call into question the received wisdom regarding Congress’s role in governance. Whereas scholars focused on the political branches’ formal powers see Congress as a branch in decline, a more nuanced picture emerges when one also considers “soft powers,” like oversight. These findings offer a blueprint for greater congressional involvement in administration: to increase Congress’s role in governance, committee membership rosters should be representative of the larger legislature and committees with overlapping jurisdictions should be established. By redesigning its internal structure, Congress can promote more frequent oversight and, because oversight can be consequential, thereby strengthens Congress as a check on presidential administration.
Keywords: Congressional oversight; Separation of powers; Governance; Agency oversight; Administrative state; Political control; Agency action